De maat genomen. De Nederlandse economie in de negentiende eeuw - Griffiths, R.T.; Jong, J. de (BMGN - Low Countries Historical Review, 2002)
Taking Stock. The Dutch economy in the Nineteenth CenturyThe publication entitled Nederland, 1780-1914. Staat, Instituties en Economische Ontwikkeling [The Netherlands, 1780-1914. The State, Institutions and Economic Development] is the culmination of a large-scale project called the Reconstruction of the Dutch National Accounts. The analyses are based on new data generated by the project. The results confirm firstly the occurrence of economic growth during the first half of the 19th century and, secondly, that the process of modern economic growth originated around 1860. Furthermore, the book stands out for its analysis of the interaction between politics and the economy. However, there are mistakes and inconsistencies in the way the statistics, on which the analyses are based, are presented. Also, the absence of any international comparisons in the book represents a missed opportunity. This review is part of the discussion forum Nederland 1780-1914 (J.L. van Zanden, A. van Riel).